Issues and challenges in the surgical treatment of anterior abdominal wall hernias. Review - Tarasiuk, T. V. (General Surgery, 2023)
The literature review discusses contentious issues and challenges that arise in the surgical treatment of anterior abdominal wall hernias. The author identified the causes of hernia formation and examined the dynamics of change in the pattern of hernia incidence. An analysis of the factors that contribute to the development of incisional ventral hernias was given special consideration. The causes of hernia recurrence were also studied. The entire spectrum of existing classifications of primary and incisional ventral hernias was reviewed, along with their advantages and disadvantages. Evaluation of current recommendations regarding the use of additional imaging methods for the examination of patients with ventral hernias was carried out. In the study, considerable attention was paid to surgical methods for hernia treatment. The advantages and disadvantages of “open” and minimally invasive laparoscopic hernioplasty techniques were critically evaluated. The difficulties in selecting an intervention method for certain types of hernias, including large ones, were highlighted, as was the importance of preventing hernia recurrence. It has been established that there are still many unsolved problems in the surgical treatment of anterior abdominal wall hernias. The author justified the need for a standardized approach to determining the characteristics of anterior abdominal wall hernias and their further classification. It is necessary to study the effectiveness of using imaging methods (ultrasound, computed tomography) for ventral hernias, depending on their size and location. There is a need for wider implementation of laparoscopic hernioplasty techniques, and the degree of the hernial defect should be taken into account when determining the indications for surgical intervention. The possibility of using laparoscopic hernioplasty for large hernias, as well as for hernias associated with rectus abdominis diastasis, requires further investigation. Improving management strategies for patients with anterior abdominal wall hernias is critical in order to reduce the risk of hernia recurrence and complications.